ANALYSIS OF THE FORM OF RECEIVABLES AND ACCOUNTS PAYABLES OF ENTERPRISES AND ORGANIZATIONS IN THE REPUBLIC OF UZBEKISTAN FOR THE QUARTER OF 2024 - Khalikulova Yulduz Panji qizi; Abdullayeva Fazilat Khazratovna (Innovation Science and Technology, 2025)
This article analyzes public and private enterprises operating in the Republic of Uzbekistan, focusing on the frst and second quarters of 2023 compared to the same periods in 2024. The study examines factors inﬂuencing the excess of accounts receivable and identifes the causes of increasing accounts payable. Furthermore, several recommendations are proposed to mitigate the growth of larger accounts payable in the future.